2014
DOI: 10.5194/bg-11-6159-2014
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling the response of forest and grassland energy exchange to heatwaves under idealized land–atmosphere coupling

Abstract: Abstract. This study investigates the difference in land-atmosphere interactions between grassland and forest during typical heatwave conditions in order to understand the controversial results of Teuling et al. (2010) (hereafter T10), who found the systematic occurrence of higher sensible heat fluxes over forest than over grassland during heatwaves. With a simple but accurate coupled land-atmosphere model, we show that existing parametrizations are able to reproduce the findings of T10 for normal summer and h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 28 publications
3
40
0
1
Order By: Relevance
“…Such differences are large enough to impact the growth and properties of the ABL. Differences in the partitioning of available energy also drive ABL dynamics and the timing of the onset of shallow cumulus formation11, but they might be of less importance than albedo differences9. Nonetheless, our results are consistent with observed higher sensible heat fluxes over temperate forest4, leading to a growing ABL and a forest breeze.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Such differences are large enough to impact the growth and properties of the ABL. Differences in the partitioning of available energy also drive ABL dynamics and the timing of the onset of shallow cumulus formation11, but they might be of less importance than albedo differences9. Nonetheless, our results are consistent with observed higher sensible heat fluxes over temperate forest4, leading to a growing ABL and a forest breeze.…”
Section: Discussionsupporting
confidence: 86%
“…We can reconcile our results with studies over Amazonia1819 by recognizing that in both cases higher sensible heat fluxes trigger preferred cloud formation423. Although this may seemingly contradict the cooler LSTs over forest, differences in roughness prevent LST from being a direct measure of sensible heat flux and temperature-sensitive flux partitioning over forest49 might not be independent of cloud cover conditions. It should be noted that both a lifting mechanism (provided by sensible heat flux) and sufficient moisture (provided by latent heat flux) are required for development of convective clouds.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…This model simulates how vegetation and the diurnal boundary layer interact by making use of idealized atmospheric profiles. We maintained early morning relative humidity across a range of early morning temperatures, such that the specific humidity profile changed with temperature (van Heerwaarden & Teuling, ). A latitude of 50°N was used as representative for European midlatitude heat waves.…”
Section: Methodsmentioning
confidence: 99%
“…By controlling the opening of their leaf stomata in response to several environmental variables (including soil moisture and VPD), plants can either enhance and reduce evapotranspiration in response to an increased VPD depending on air dryness and temperature (Figure ). Using the simplified land‐atmosphere model, van Heerwaarden and Teuling () showed that the observational results of Teuling et al () could be reproduced by assuming that forest stomata close in response to high VPD during heat waves, whereas grasses do not. Sulman et al () similarly found that observed evaporation in a mixed forest responded to both VPD and soil moisture anomalies with similar magnitudes, but the timescales of VPD response (hours) was much shorter than the soil moisture response (multiple days or weeks).…”
Section: Introductionmentioning
confidence: 99%